Study on the effect of black cumin Oil and LDL on lipopol ysaccharide (lps) - induced toll - like receptor activation in macrophage and dendritic cell lines - Hamid, Shahrul Bariyah Sahul (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2011)
Lipid-laden macrophage has been reported to play various roles in atherogenesis. The focus was to elucidate effects of a natural product on the progression of monocytederived macrophage growth. Nigella saliva was selected as a form of treatment to macrophage cell growth in culture conditions due to various findings on its medical benefits. Human monocytes were isolated and grown at 37°C and 5%C02 saturation for 5 days prior to treatment with Nigella sativa oil. The cells were plated and washed before addition of ox-LDL (lOμg/ml) alone in untreated condition and combination of ox-LDL (lOμg/ml) and (72 μg/ml) Nigella sativa oil in treated condition. The growth progression was monitored every 24 hours for 3 days. Nigella sativa oil caused noticeble effect on macrophage growth compared to monocyte especially 24 hours after treatment. The mean was significant different between untreated and treated condition for both monocytes and macrophages (p<0.001). This was shown by the delayed growth pattern as seen in macrophage compared to monocytes. There was less oil red 0 staining in cells treated with mixture of oxLDL and Nigella sativa compared to those treated with oxLDL alone. The signalling of Nigella saliva has been reported to occur via TLR-4 receptor, where it is significantly present on macrophage cell surface. This may be one of the factors leading to the growth difference. Hence, progression of macrophage to foam cells could possibly be controlled with the use of Nigella saliva oil.